Bedding material properties and slurry C/N ratio affect the availability of nitrogen in cattle slurry applied to soil - Andersson, Karin; Dahlin, A. Sigrun; Sørensen, Peter; Delin, Sofia (Frontiers in Sustainable Food Systems, 2024)
Introduction Cattle slurry used as fertilizer in crop production is a mix of feces, urine, water, and bedding material from the housing system. Previous studies have shown that slurry nitrogen (N) availability to crops is dependent on C/N ratio. As the bedding material can contribute a significant part of total slurry carbon (C), its characteristics may affect the C/N ratio of the slurry. There is increasing interest in using the solid fraction from mechanical slurry separation as bedding material, and therefore this study investigated the potential effect of this fraction on slurry N availability, compared with more commonly used bedding materials such as straw and sawdust. Methods In two parallel 28-day laboratory incubations, net mineral N release and C mineralization from slurries applied to sandy loam soil were measured. The slurries comprised a liquid fraction (LF) from mechanical cattle slurry separation with a screw-press and different added bedding materials. Liquid fraction was mixed with two types of bedding material, solid slurry fraction (SF) and chopped straw, in different proportions, resulting in C/N ratios of 10, 12, and 14 in the slurry. In additional treatments, two other bedding materials, ground straw and sawdust, with slurry C/N ratio 12, were used. Results For SF and chopped straw, similar negative linear correlations were seen between slurry C/N ratio and net mineral N release after 28 days. Carbon mineralization, expressed as a percentage of total C added, was higher from the mixture containing SF than that containing straw, while no clear relationship with C/N ratio was found. At slurry C/N ratio 12, net release of mineral N was 28–39% of total N and decreased in the order: sawdust>chopped straw=SF=ground straw. Net C mineralization at the same slurry C/N ratio was 33–46% and decreased in the order: SF=ground straw>chopped straw>sawdust. Discussion For bedding materials with similar fiber composition (i.e., SF and straw), differences in C availability due to particle size or degree of degradation by microorganisms did not influence slurry N availability measurably. For sawdust, with high lignin content, the results indicate that limited C availability may lead to lower slurry N immobilization.